Persepsi Mahasiswa Terhadap Kualitas Pembelajaran Prodi Ilmu Agama Dan Kebudayaan S2 Pascasarjana STAHN Mpu Kuturan Singaraja - Mahardika, Gede; Hadriani, Ni Luh Gede; Atmadja, Nengah Bawa (Widya Sandhi, 2024)
This research aims to describe and analyze the quality of learning in the Postgraduate Religious and Cultural Sciences Study Program at the Mpu Kuturan Singaraja State Hindu Religion College. This research use desciptive qualitative approach. This research was carried out in the second semester of the 2022/2023 academic year. Data collection in this research was carried out by distributing questionnaires online using a Google form to all students of the Religious and Cultural Sciences Study Program Postgraduate STAHN Mpu Kuturan Singaraja, interviews and focus group discussions. The results of the research show that 75% of students' perceptions of the quality of learning in the Master of Religion and Culture Study Program Postgraduate STAHN Mpu Kuturan Singaraja were satisfied. Student satisfaction can be seen from three aspects, including: the quality of the teaching and learning process, administrative governance and availability of infrastructure.